2015
DOI: 10.1108/jhtt-01-2015-0002
|View full text |Cite
|
Sign up to set email alerts
|

Mobile application for the timeshare industry

Abstract: Purpose – The purpose of this study is to examine consumer perceptions toward the adoption of mobile technology within the vacation ownership/timeshare segment of the hospitality industry. Despite the proliferation of mobile applications in the greater hospitality and tourism industry, few timeshare companies use this technology. However, customers have expressed strong intentions to use technology. Therefore, this study examines consumers’ attitudes toward and experiences with mobile applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 54 publications
2
15
0
2
Order By: Relevance
“…It is important to note that this paper investigated both the relationship between privacy concerns and attitude towards app purchase and the relationship between privacy concern elements and apps purchase intention, which is one of the significance of this research. While numerous studies investigated app purchase intention instead of attitude, several of these studies found that attitude toward technology and intention to use IT are positively related [49].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that this paper investigated both the relationship between privacy concerns and attitude towards app purchase and the relationship between privacy concern elements and apps purchase intention, which is one of the significance of this research. While numerous studies investigated app purchase intention instead of attitude, several of these studies found that attitude toward technology and intention to use IT are positively related [49].…”
Section: Discussionmentioning
confidence: 99%
“…인지된 위험은 불확실한 상황에서 의사결정에 대한 잠재적 손실에 대한 평가를 의미하며 (Gupta et al, 2004), 인지된 무리 행동은 다른 사람의 의사결정을 모방하 고자 하는 정도로 정의할 수 있다 (Bonabeau, 2004 (Ooi & Tan, 2016;Ryu et al, 2018). 또한, 모바일 내에서 앱 카드를 설치하는 방법이 간단하 고, 개인정보 등록 절차도 간소화되어 쉽고 편리한 서비스로 인 식되고 있다 (Johnson et al, 2018;Slade et al, 2013 (Ding & Li, 2019;Ha et al, 2016;Huang & Chen, 2006;Jiang et al, 2018 (Ajzen, 1991 (Elkaseh et al, 2016;Kim, 2010;Lee et al, 2015;Rivera et al, 2015;Talke & Heidenreich, 2014 (Kwon & Lim, 2012;Yoon et al, 2014), 다양한 인지 요소들에 의해 영향을 받는 혁 신에 대한 개인의 부정적 태도로 확인되었다 (Chen, 2008;Ding & Li, 2019;Huang & Chen, 2006;Raza et al, 2017).…”
Section: A-b-c 모델unclassified
“…인지된 유용성은 혁신에 대한 태도와 중 요한 상관 관계가 있는 것으로 나타났으며, 인지된 유용성이 현 재 이용하고 있는 서비스와 새롭게 도입된 서비스에 대한 태도에 영향을 미치는 것으로 나타났다(Elkaseh et al, 2016;Rivera et al, 2015). 인지된 유용성이라는 소비자의 인지적 요소가 혁신 에 대한 소비자 태도에 영향을 미치는 것으로 나타났으며(Rivera et al, 2015;Venkatesh et al, 2003), 인지된 유용성과 현재 이용하고 있는 제품 만족도 간의 인과관계를 살펴본 연구에서 인 지된 스마트폰의 유용성과 일반 휴대폰이라는 현재 제품에 대한 만족도가 부(-)적 관계에 있는 것으로 나타났다(Kwon & Lim, 2012). 또한, 혁신의 인지된 유용성과 소비자 태도 간의 관계를 살펴본 연구에서 인지된 유용성이 혁신에 대한 소비자 태도를 증 가시키거나 감소시키는 선행 요인으로 확인되었다(Elkaseh et al, 2016).…”
unclassified
“…This emotional reaction can occur at any time as positive or negative moments. Individual mobility is defined as the extent to which a person uses or seeks a service in almost all activities and situations [9,12,13]. The use of smartphones and internet applications by Indonesian travelers has caused disruption in the tourism sector.…”
Section: Theoretical Backgroundmentioning
confidence: 99%